Trophic Status of the Koto Tibun Reservoir, Kampar District, Riau Province Based on Trophic Index (TRIX) - Irwan Nababan; Clemens Sihotang; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract  Koto Tibun Reservoir receivedwater from the Tibun River.In the area around the upstream of the river, however, there are many human activities that nutrient the river and as a consequence affects the trophic status of the dam. To understand the trophic status of the dam based on Trophic Index (TRIX), a research was conducted in February – March 2018. There were 3 sampling stations namely Station 1 (riverine zone), Station 2 (transition zone) and Station 3 (lacustrine zone). Samples were taken once/week. Water quality parameters measured were DIN (Dissolved Inorganic Nitrogen), total phosphorus, dissolved oxygen, chlorophyll-a, transparency, temperature and pH. Results shown that the transparency was 75.3–78.6cm, temperature 25.5–25.80C, pH 5, total phosphorus 0.13–0.19 mg/L, DIN 0.45–0.50 mg/L, chlorophyll-a 3.10–3.97 μg/L and oxygen saturation 57.17–68.17 %. The TRIX value ranged from 2 to 2.5 and indicates that the Koto Tibun Reservoir can be categorized as mesotrophic. Keyword :Koto Tibun Dam, Water quality, Nutrient, Mesotrophic